2012
DOI: 10.5539/ijbm.v7n5p31
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Economic Characteristics of HIV in a South African Prison

Abstract: South Africa has placed increased importance on addressing the HIV/AIDS epidemic and has identified people in prisons as one of several high risk groups. Despite this emphasis, respective departments have not pursued the task of data collection at all vigorously. A sample of 274 volunteer inmates was drawn from the Westville Maximum Security Prison, Durban, KwaZulu-Natal Province. A probit model was used and the data analysed to establish statistically significant risk factors for transmission of HIV and impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
1
1
Order By: Relevance
“…The overall prevalence in this sample is lower than the 2015 South African general population's HIV prevalence of 19.2% among people 15 to 49 years of age [1], and lower than the findings of a 2012 paper that described a 29.6% prevalence in one South African prison [14]. It is possible that intensive investment of resources within DCS and beyond has resulted in a lowered HIV prevalence and incidence, as has been demonstrated in other settings [15,16], though given that the majority of HIV diagnoses in the study population were unknown prior to this screening campaign, it is unlikely that the lower prevalence compared to the general population is the result of such an investment.…”
Section: Discussioncontrasting
confidence: 67%
“…The overall prevalence in this sample is lower than the 2015 South African general population's HIV prevalence of 19.2% among people 15 to 49 years of age [1], and lower than the findings of a 2012 paper that described a 29.6% prevalence in one South African prison [14]. It is possible that intensive investment of resources within DCS and beyond has resulted in a lowered HIV prevalence and incidence, as has been demonstrated in other settings [15,16], though given that the majority of HIV diagnoses in the study population were unknown prior to this screening campaign, it is unlikely that the lower prevalence compared to the general population is the result of such an investment.…”
Section: Discussioncontrasting
confidence: 67%
“…Recent research done at Westville Correctional Services centre showed an HIV sero-prevalence rate of almost 30%. 13 This high prevalence of HIV in prisons is an area of great concern due to the fact that HIV is readily transmissible in prisons (due to factors such as overcrowding, gangsterism, etc) and because HIV is implicated as an aetiological agent in major mental disorders. 14 …”
Section: Prevalence Ratesmentioning
confidence: 99%